Audience Africa : social development : Africa's priorities : final report (UNESCO ParisFR, 1995)
States Africa's position on the question of development in the areas of education, science, technology and sustainable development, regionalization, rural development and democracy.
Document prepared for Copenhagen World Summit for Social Development